Pengaruh Kepemilikan Institusional dan Kepemilikan Asing terhadap Agresivitas Pajak pada Perusahaan Sektor Energi - Shefina Auliya Putri; Wahyu Helmy Dimayanti Sukiswo (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the influence of institutional ownership and foreign ownership on tax aggressiveness in energy sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The sector was chosen because commodity price fluctuations can potentially trigger tax aggressiveness practices alongside rising operational profits. This research uses a quantitative approach utilizing secondary data from company financial statements and annual reports. The purposive sampling method resulted in twenty-eight companies and one hundred twelve total observations over four years. Data analysis was performed using panel data regression with the Common Effect Model via the EViews 12 software. The results clearly prove that institutional and foreign ownership significantly influence tax aggressiveness, both partially and simultaneously. This indicates that institutional and foreign investor ownership structures effectively perform a strict monitoring function over management, ensuring companies are more cautious in determining tax policies to optimally and efficiently suppress tax aggressiveness practices.